PENGARUH ACCOUNT REPRESENTATIVE (AR) TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada KPP Pratama Kepanjen) - Rachmawati, An'nissa Dwi (Jurnal Mahasiswa Perpajakan, 2014)
The government do tax reform, make a â€œPrimaâ€ Services with forming account representative in â€œKPP Modernâ€. Account Representative have many function, there are education, mentoring, and controlling which are anticipated have an effect on taxpayer compliance. The purpose of this research is to know the simultan and partial influence of education, mentoring, and Controlling of Account Representative to taxpayer compliance. Types of research used in this study is explanatory research with quantitative approach. Samples used in this study as many as 100 respondents tax payer with questionnaire research instruments. Analysis of the data used in this research using descriptive analysis and multiple linear analysis. The results showed that Education Variables (X1), Mentoring Variable (X2), and Controlling of Account Representative Variable (X3) effected on Personal Tax Payer Compliance. In this study it can be seen also that individually (partial) the third variables involves Education Variables (X1), Mentoring Variable (X2), and Controlling of Account Representative Variable (X3) has a positive influence on Personal Tax Payer Compliance. The dominant variable in the Personal Tax Payer Compliance is controlling variables with the highest Beta 0,262. Keywords: Education, Mentoring, Controlling, Account Representative, Tax Compliance